2016
DOI: 10.15283/ijsc.2016.9.1.107
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine Effectively InduceshTERTGene Expression of Human Adipose Tissue-derived Mesenchymal Stem Cells Obtained from the Aged Subjects

Abstract: Background and ObjectivesHuman mesenchymal stem cells (hMSCs) are attractive candidates for cell therapy and regenerative medicine due to their multipotency and ready availability, but their application can be complicated by the factors such as age of the donors and senescence-associated growth arrest during culture conditions. The latter most likely reflects the fact that aging of hMSCs is associated with a rise in intracellular reactive oxygen species, loss of telomerase activity, decrease in human telomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Following incubation for 4 h, the supernatant was removed and 100 μL of dimethyl sulfoxide was added to each well. The optical density of each well was measured in an ELISA Reader (Labsystems, Helsinki, Finland) at a wavelength of 570 nm [5, 8]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following incubation for 4 h, the supernatant was removed and 100 μL of dimethyl sulfoxide was added to each well. The optical density of each well was measured in an ELISA Reader (Labsystems, Helsinki, Finland) at a wavelength of 570 nm [5, 8]. …”
Section: Methodsmentioning
confidence: 99%
“…A great deal of evidence suggests that osteoporosis results from the interaction of genetic susceptibility and environmental factors [4]. Among which, zinc ion (Zn +2 ) as an essential trace element, was reported to be involved in the pathogenesis of osteoporosis and has direct effect on bone mineralization [58]. It has been reported that the administration of zinc sulphate (ZnSO 4 ) to weanling rats for 3 days resulted in a statistically significant increase in bone development [9].…”
Section: Introductionmentioning
confidence: 99%
“…The stock MTT dye solution (2 mg/mL) was added to each well after the plates were incubated at 37ºC in a 5 % CO 2 incubator for 4 h. Following incubation for 4 h, the supernatant was removed and 100 µL of dimethyl sulfoxide was added to each well. The optical density of each well was measured in an ELISA Reader (Labsystems, Helsinki, Finland) at a wavelength of 570 nm [19].…”
Section: Determining Suitable Concentration Of Curcumin By Mtt Assaymentioning
confidence: 99%
“…Stem cells are uncommitted cells that have potential to differentiate into specialized cell types (Nejati‐Koshki et al ., ). They are able to maintain renewal activity by asymmetric cell divisions (Nejati‐Koshki et al ., ; Farahzadi et al ., ). Also, stem cells have opened new era in the field of developmental biology and regenerative medicine.…”
Section: Stem Cells Characteristics At a Glancementioning
confidence: 97%